2020
DOI: 10.1111/evo.14111
|View full text |Cite|
|
Sign up to set email alerts
|

Long‐term cloud forest response to climate warming revealed by insect speciation history*

Abstract: Montane cloud forests are areas of high endemism, and are one of the more vulnerable terrestrial ecosystems to climate change. Thus, understanding how they both contribute to the generation of biodiversity, and will respond to ongoing climate change, are important and related challenges. The widely accepted model for montane cloud forest dynamics involves upslope forcing of their range limits with global climate warming. However, limited climate data provides some support for an alternative model, where range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…Our demographic modelling approach suggested that events of interspecific gene flow also occurred during the late Pleistocene (~16.1 kya), probably as a consequence of population expansions during the transition between the last maximum glacial and early Holocene (e.g. Salces‐Castellano et al, 2021; Rodriguero et al, 2016; Tonzo et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…Our demographic modelling approach suggested that events of interspecific gene flow also occurred during the late Pleistocene (~16.1 kya), probably as a consequence of population expansions during the transition between the last maximum glacial and early Holocene (e.g. Salces‐Castellano et al, 2021; Rodriguero et al, 2016; Tonzo et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…Existing studies in this area have been limited to specific arthropod lineages, such as beetles or spiders, for which conventional taxonomical and molecular processing is time-consuming (e.g. Malumbres-Olarte et al, 2021;Antonia Salces-Castellano et al, 2020). HTS barcoding provides an opportunity to increase both the taxonomic and geographic scale of arthropod community sampling.…”
Section: Island Community Assembly Of Arthropod Biodiversitymentioning
confidence: 99%
“…However it has been shown that, across multi-species comparisons, potentially idiosyncratic single marker signals within a subset of arthropod species may be outweighed by common community level signatures (e.g. Salces-Castellano et al, 2020;Scalercio et al, 2020). As the histories of individual species complexes may themselves be idiosyncratic, having noisy data across hundreds or even thousands of species may, in some cases, be more revealing of general patterns and processes in a region than deeper sequencing of a more limited number.…”
Section: Drivers Of Island Arthropod Speciationmentioning
confidence: 99%
“…In this issue, Salces‐Castellano et al. (2020) searched for clues to the connectivity dynamic of a cloud forest in an oceanic island by analyzing the evolutionary history of two populations of a beetle species tightly associated with this ecosystem. The authors proposed a novel framework to test the effect of climatic fluctuations on montane ecosystems connectivity by harnessing genomic information.…”
Section: Figurementioning
confidence: 99%